Effects of Ketoconazole on the Pharmacokinetics of Ponatinib in Healthy Subjects - Narasimhan, Narayana I.; Dorer, David J.; Niland, Katie; Haluska, Frank; Sonnichsen, Daryl (Journal of clinical pharmacology, 2013)
Ponatinib is a BCR‐ABL tyrosine kinase inhibitor (TKI) approved for the treatment of chronic myeloid leukemia and Philadelphia chromosome–positive acute lymphoblastic leukemia in patients resistant or intolerant to prior TKIs. In vitro studies suggested that metabolism of ponatinib is partially mediated by CYP3A4. The effects of CYP3A4 inhibition on the pharmacokinetics of ponatinib and its CYP3A4‐mediated metabolite, AP24567, were evaluated in a single‐center, randomized, two‐period, two‐sequence crossover study in healthy volunteers. Subjects (N = 22) received two single doses (orally) of ponatinib 15 mg, once given alone and once coadministered with daily (5 days) ketoconazole 400 mg, a CYP3A4 inhibitor. Ponatinib plus ketoconazole increased ponatinib maximum plasma concentration (Cmax) and area under the concentration–time curve (AUC) compared with ponatinib alone. The estimated mean ratios for AUC0–∞, AUC0–t, and Cmax indicated increased exposures to ponatinib of 78%, 70%, and 47%, respectively; exposure to AP24567 decreased by 71%. Exposure to AP24567 was marginal after ponatinib alone (no more than 4% of the exposure to ponatinib). These results suggest that caution should be exercised with the concurrent use of ponatinib and strong CYP3A4 inhibitors and that a ponatinib dose decrease to 30 mg daily, from the 45 mg daily starting dose, could be considered.